Model Logika Fuzzy Tsukamoto Dalam Perancangan Sistem Informasi Sebaran Industri Kecil dan Menengah Kabupaten Bondowoso - Nugroho Setyo Wibowo; Erna Selviyanti; Wenny Dhamayanti (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2022)
The existence of the COVID-19 pandemic and the global economic crisis did not affect the existence of Small and Medium Industries and even experienced relatively stable growth. Small and Medium Industries in the manufacturing sector were able to realize an investment value of up to IDR 72.3 trillion in the third quarter of 2020. In the context of creating competitive Small and Medium Industries, strengthening the national industrial structure, alleviating poverty, expanding job opportunities, and producing industrial goods and/or services for export purposes, the strategic role of Small and Medium Industries needs to be increased through the digitization of Small and Medium Industries. This study uses Fuzzy Tsukamoto's logic calculations in making the membership function of the distribution area of ​​Small and Medium Industries in Bondowoso Regency. From the Fuzzy Logic model obtained, an information system design for the distribution of Small and Medium Industries can be made in the form of context diagrams and interface designs. From this design, it will be easier for the Bondowoso Regency Cooperatives and Industry Office to develop a web and mobile-based application in the context of the process of digitizing Small and Medium Industries. The existence of this information system will provide benefits for the Office of Cooperatives, Industry and Trade as well as Small and Medium Industry players in Bondowoso Regency, not only being able to visualize the distribution of Small and Medium Industries but also being able to provide an overview of Small and Medium Industry parameter data that can be used as decision makers. decisions for existing stakeholders.